2018
DOI: 10.1016/j.atherosclerosis.2018.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and progression of subclinical atherosclerosis in patients with chronic kidney disease and diabetes

Abstract: Subclinical atherosclerosis is more prevalent, carries a higher plaque burden and is more rapidly progressive in renal patients with diabetes. In these patients, diabetes outweighs other described risk factors associated with the presence of subclinical atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The criteria used to make the diagnosis of diabetes and, thus, to include a individual in the diabetes group have been reported previously [17]. The criteria used were as follows: a previous diagnosis of diabetes recorded in the individual’s medical history, a fasting plasma glucose ≥ 126 mg/dl or HbA1c ≥ 6.5% determined by laboratory testing or a current prescription of any anti-diabetic drug.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria used to make the diagnosis of diabetes and, thus, to include a individual in the diabetes group have been reported previously [17]. The criteria used were as follows: a previous diagnosis of diabetes recorded in the individual’s medical history, a fasting plasma glucose ≥ 126 mg/dl or HbA1c ≥ 6.5% determined by laboratory testing or a current prescription of any anti-diabetic drug.…”
Section: Methodsmentioning
confidence: 99%
“…To date, there is limited evidence describing the specific prevalence of SA in individuals with both diabetes and CKD. Recently, our group reported that SA is more prevalent, carries a higher plaque burden and is more rapidly progressive in individuals with CKD and diabetes [17]. In addition, our group also reported that renal individuals show a higher prevalence of plaques [18, 19] and a higher incidence of future CVEs across all stages of CKD compared with controls [20].…”
Section: Introductionmentioning
confidence: 93%
“…CKD patients have more severe atherosclerosis than age-and sex-matched controls from the general population [6]. The NEFRONA study has indicated that the incidence rates of carotid atherosclerosis are 50.8% in patients with CKD and 69% in diabetic patients with CKD [16]. Currently, antiplatelet drugs are widely used to prevent CVD, especially intravascular thrombosis.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Chronic kidney disease (CKD) is an independent risk factor for cardiovascular disease (CVD) and atherosclerosis [1]. Atherosclerosis is more prevalent in CKD patients, and it also causes more comorbidities in CKD patients [2]. Studies have produced controversial results as to the independence of CKD indexes as risk factors for atherosclerosis among other atherosclerosis risk factors.…”
Section: Introductionmentioning
confidence: 99%